2005
DOI: 10.1002/cne.20532
|View full text |Cite
|
Sign up to set email alerts
|

Species and sex differences in brain distribution of corticotropin‐releasing factor receptor subtypes 1 and 2 in monogamous and promiscuous vole species

Abstract: Corticotropin-releasing factor (CRF) receptor subtypes 1 and 2 have been implicated in rodent models of anxiety, but much less is known about the CRF system and social behavior. Both corticosterone and central CRF receptors modulate pair bonding in the monogamous prairie vole. Using receptor autoradiography, we mapped CRFR(1) and CRFR(2) in the brains of two monogamous vole species, the prairie vole and pine vole, and two promiscuous vole species, the meadow vole and montane vole. We found markedly different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
113
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(122 citation statements)
references
References 51 publications
9
113
0
Order By: Relevance
“…Consistent with this hypothesis are data from rats showing a more pronounced habituation of corticosterone responses to chronic restraint stress in males versus females (Galea et al, 1997). Sex differences in the central synthesis or effects of other neuropeptides, including vasopressin (DeVries & Simerly, 2002;DeVries & Panzica, 2006) or CRF (Lim et al, 2005;Lim et al, 2006), may also mediate the neuroendocrine responses described here.…”
Section: Discussionsupporting
confidence: 84%
“…Consistent with this hypothesis are data from rats showing a more pronounced habituation of corticosterone responses to chronic restraint stress in males versus females (Galea et al, 1997). Sex differences in the central synthesis or effects of other neuropeptides, including vasopressin (DeVries & Simerly, 2002;DeVries & Panzica, 2006) or CRF (Lim et al, 2005;Lim et al, 2006), may also mediate the neuroendocrine responses described here.…”
Section: Discussionsupporting
confidence: 84%
“…The present findings for 125 I-SG demonstrate that putative CRF receptors in songbirds are distributed in a pattern very similar to mammals (Primus et al, 1997;Sanchez et al, 1999;Van Pett et al, 2000;Lim et al, 2005), with 125 I-SG binding sites being found throughout the pallium, striatum, extended amygdala, and various regions of the hypothalamus. However, in contrast to mammals, binding in the septal nuclei was largely restricted to the posterior septum (commissural septal nucleus and nucleus of the pallial commissure).…”
Section: Neuropeptide Receptors In Songbirds and Other Vertebrate Groupssupporting
confidence: 61%
“…Interestingly, these studies have also shown that species-specific densities of V 1a receptors in brain areas other than the ventral pallidum do not correlate with mating system, suggesting that adaptive receptor functions remain to be elucidated that are independent of mating system (review: Goodson and Bass, 2001). A similar observation is made for CRF receptors in voles (Lim et al, 2005). We hypothesize that these other adaptive functions include the regulation of sociality, thus the present studies focus on the evolution of species-typical group size and its relationship to neuropeptide receptor densities.…”
mentioning
confidence: 80%
See 2 more Smart Citations